2011
DOI: 10.1002/bjs.7517
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic resection with transanal specimen extraction for sigmoid diverticulitis

Abstract: Transanal specimen extraction in addition to per ano transcolonic stapler anvil insertion allows laparoscopic sigmoid resection to be performed with just three ports. Although intraperitoneal bacterial contamination occurs, this does not appear to translate into infectious morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 26 publications
(36 reference statements)
1
49
1
Order By: Relevance
“…All patients were commenced on ambulatory physiotherapy and tolerated oral intake by the first post-operative day, and all met discharge criteria by the third post-operative day. There were no incidences of anastomotic leaks, fissures, or deterioration of anal continence as measured by Wexner scores immediately post-operatively and during outpatient review over a median follow-up of 9 months (range, [8][9][10][11]. The two oldest patients had preoperative Wexner scores of '1', remaining unchanged postoperatively.…”
Section: Resultsmentioning
confidence: 91%
“…All patients were commenced on ambulatory physiotherapy and tolerated oral intake by the first post-operative day, and all met discharge criteria by the third post-operative day. There were no incidences of anastomotic leaks, fissures, or deterioration of anal continence as measured by Wexner scores immediately post-operatively and during outpatient review over a median follow-up of 9 months (range, [8][9][10][11]. The two oldest patients had preoperative Wexner scores of '1', remaining unchanged postoperatively.…”
Section: Resultsmentioning
confidence: 91%
“…45,46 One prospective study found no infection-related complications after transanal specimen extraction for diverticulitis despite positive polymicrobial peritoneal cultures. 47 Furthermore, anal sphincter function was not negatively impacted by transanal NOSE, 48,49 with patients reporting significant improvement in their quality of life at 6-month follow up. 50 Overall, based on these few non-randomized NOSE studies, transvaginal and transanal extraction of colorectal resection specimens appears to be safe, associated with reduced pain and shorter LOS, and offering at least the cosmetic benefit of eliminating extraction site incisions.…”
Section: Natural Orifice Specimen Extractionmentioning
confidence: 89%
“…Recently, several studies have confirmed the safety and feasibility of laparoscopic resection with NOSE for the treatment of colorectal disease [9][10][11][12][13][14][15]. However, conflicting conclusions stating that NOSE may increase the possibility of peritoneal contamination have also been yielded [16,17]. Whether laparoscopy with NOSE is desirable to maximize the benefits of minimally invasive surgery and to minimize the risks of postoperative complications is not known.…”
Section: Introductionmentioning
confidence: 98%